The biodiversity and description of microbiota in traditionally fermented milk products: a study in rural South Africa - de Waal, Pieter Johannes (Department of Paediatrics and Child Health, 2021)
The rapid rise in allergic diseases has been linked to urbanization and Westernization. Recent observational studies indicate a significantly lower prevalence of allergic disease in children exposed to farming environments during the ante- and postnatal period. Consumption of unpasteurized and fermented cow's milk have been hypothesized as independent protective factors against allergy. Lack of microbial diversity and low levels of lactic acid producing bacteria (LAB) in infant diets may be predisposing factors to developing atopic eczema, allergic sensitisation and asthma. In South Africa, rural communities with a low prevalence of allergy consume unpasteurized and traditional fermented milk products on a regular basis. The objective of this study was to characterize and compare the microbiome of differently sourced cow's milk samples. Raw, unpasteurized cow's milk was collected from farms in an urban and rural setting, respectively. Another sample, collected from a cow on a rural farm, was left to naturally ferment (amasi) while three different brands of commercially fermented milk samples were obtained from a local retail shop. The variable V3 and V4 regions of the 16S rRNA gene were amplified and diversity and abundance plots were constructed and analyzed. Clear differences in the diversity and abundance of especially LAB in the differently sourced samples were demonstrated. Urban, and rural fresh cow's milk samples were the most diverse, and commercially bought products, the least. The commercially fermented products were similarly dominated by LAB, belonging to the phylum Firmicutes (more than 98% abundance) and the phylum Proteobacteria (less than 2% abundance). The homemade fermented milk (amasi) comprised approximately 50% Firmicutes and approximately 50% Proteobacteria. At the family member level, Leuconostocaceae dominated in all three the commercially bought samples. At the species level, Lactococcus lactis (AB100803) dominated in all the milk products, with less abundance in the fresh cow's milk samples. Lactobacillus paracasei (D79212) and Streptococcus infantis (AY485603) were abundant in amasi and absent in the commercially fermented products. Statistically significant difference between fermented and unfermented cow's milk samples at species level were demonstrated. Lactococcus chungangensis (EF694028), Leuconostococcus mesenteroides (AB023247) and Leuconostococcus pseudomesenteroides (AB023237) were abundant in the commercially fermented products, but absent in amasi. Important pathogens were identified in fresh cow's milk and amasi. We concluded that commercially fermented milk, although of low diversity, may be utilized as a safe allergy protective weaning food in infant diets. The microbiome of homemade amasi is more diverse than commercially fermented products and important allergy protective lactic acid producing organisms were identified in this study. However, the safety of amasi remains a concern. This information can be used in future research to produce important allergy protective ‘starter cultures' and to appropriately shape the gut microbiome early in life.